Physeal-Sparing Anterior Cruciate Ligament Reconstruction for Skeletally Immature Patients: All-Epiphyseal Technique Using Quadricep Tendon Autograft - Hatem B. Afana; Thomas Nau (Case Reports in Orthopedics)
The anterior cruciate ligament (ACL) is a major stabilizing structure of the knee and one of the most common injured structures. The true incidence of ACL injury in children and adolescents is unknown, but recent studies suggest increased ACL injury rates, especially in the sports-participating population. The mechanism of injury, clinical examination, and diagnosis of ACL injury in children is the same as in adults. The main concerns in the management of pediatric ACL injuries are the open physes and the eventual long-term consequences of the ACL deficient knee. The ideal treatment strategy of pediatric ACL injuries is still controversial, because there is still no universal consensus for techniques, graft choices, and postoperative rehabilitation. We present a case of a 12-year-old male patient who underwent ACL reconstruction using an all-inside, physeal-sparing technique with a quadriceps tendon autograft and discuss the current treatment strategies.